Aesthetic and functionality in fixed prosthodontic: sperimental and clinical analysis of the CAD-CAM systematic 3Shape - DE VICO, G. (CIC Edizioni Internationali, 2009)
In the last 15 years the increasing aesthetic demand, push constantly industry and the clinical to entirely look for new solutions for the realization of all-ceramic crowns, with such characteristics to be used for both anterior and posterior restorations. The most greater contribution, in such sense derives from the finished progress in the computer sector, that have allowed the application of the technologies CAD-CAM, also in dentistry (2–5, 11). These systematics have allowed us to get “automatically” structures for dental prosthesis, starting from the scanning of the die and passing for an intermediary phase of computerized planning (CAD, computer aided design), through numerical control millers (CAM, computer aided manufacturing), enslaved to calculating the electronic that drives the movement of it. The aim of this work is therefore that to analyze and to describe the systematic computerized 3SHAPE verifying the degree of precision, through the analysis of the obtainable marginal closing with the zirconia frameworks.